Pediatric tracheostomy practice patterns. (June 2020) - Sioshansi, Pedrom C.; Balakrishnan, Karthik; Messner, Anna; Sidell, Douglas
Abstract: Objective: Despite recent guidelines and the frequency of pediatric tracheostomy, surgical techniques and perioperative management are variable. We aim to describe the post-operative practice patterns following tracheostomy in children. Methods: An electronic cross-sectional survey was distributed to American Society of Pediatric Otolaryngologists (ASPO) members in academic and private practice settings. Responses were collected anonymously and analyzed by percentages of respondents who employ specific management strategies. Statistical analysis of response distributions performed using the Z test of proportions for binary questions and the Mantel-Haenszel chi-square test for questions with more than two options. For questions with ordered categorical responses, Cuzick's nonparametric test of trend was used. Results: One-hundred twenty-four responses were received (22.3%). Most respondents were fellowship trained and practiced in academic medical centers. A greater number of tracheostomies were performed by respondents practicing in the Midwest region (p = 0.042). There was no variability in the number of tracheostomies performed based on practitioner age, hospital setting, or fellowship training. The majority perform stoma maturation and/or stay suture techniques intraoperatively and send patients to the intensive care unit postoperatively. The routine use of postoperative paralysis was reported by a minority of respondents and 50% reported the use of sedation. There was a roughly-even distribution of respondents who reported postoperative immobilization, mobilization to a chair, and ambulation respectively. Routine; postoperative airway evaluations were reported by 35% of respondents. Clinic follow-up was; variable. Conclusion: These results demonstrate ongoing variability in the postoperative management strategies following tracheostomy in children and highlight areas for further study.